Pelatihan Penerapan PSAK ETAP Dan GCG Pada PT Kemas Jaya Mulia Untuk Optimalisasi Taat Administrasi Keuangan Serta Budaya Kerja Prima Di Sektor Usaha Real Estate - Marisha Khanida; Muslimin Muslimin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
SMEs still have low awareness of the benefits of financial reports. If the financial report produced by the entity reflects the actual situation, then the financial report is reliable and can be used as a reference for interested parties, namely investors, government, employees and even the public. With financial reports, they can separate financial data between personal and company property. The problem in this research is the level of awareness of Small and Medium Enterprises (SMEs) in preparing financial reports. This training aims to provide knowledge regarding the application of SAK ETAP and its relevance to Good Corporate Governance which is beneficial for excellent service for a business, in this case the Real Estate sub-sector of business which is increasingly developing every year with many similar competitors.